Research on the Relationship Between Integration of Three Industries in Rural Areas and Scientific and Technological Innovation Based on VAR Model - Yingying DING; Yao HE; Ping HAO (Guangdong nongye kexue, 2022)
【Objective】With the continuous development of the information age, science and technology has become the fundamental driving force for the development of rural industries. In order to further activate the vitality of rural development and promote the integration of three industries in rural areas, it has become a strong support for rural revitalization.【Method】Based on the vector auto regression (VAR) model and relevant data of science and technology and industry in China from 2011 to 2019, the study explores the relationship between the integration of three industries in rural areas and the input of scientific and technological innovation through nine secondary indicators under three first-level indicators corresponding to the output of science and technology, the input of science and technology, and the integration of three industries in rural areas.【Result】Empirical analysis results show that, there is still a lot of room for continuous improvement in the degree of integration of three industries in rural areas. There are dynamic interactions and high correlations among the input intensity of science and technology, the output level of science and technology and the integration of three industries in rural areas in the index systems; the input of science and technology innovation can promote the development of integration of three industries in rural areas, which will increase 0.767% when the output of science and technology is increased by 1% in the current period; the development of integration of three industries in rural areas will promote further investment in science and technology innovation. When the comprehensive score of integration of three industries in rural areas increases by 0.881%, the comprehensive score of science and technology output increases by 1%.【Conclusion】Based on the above conclusions, we should focus on promoting agricultural scientific and technological innovation to overcome technical barriers, support and encourage agricultural scientific research workers to develop products and technological innovation, build a platform for scientific and technological innovation alliances, increase investment in scientific and technological research and development, create an environment for scientific research and innovation, and accelerate the pace of agricultural technological innovation in our country to realize the deep integration between traditional agriculture and high-tech industries.